The Effect of Physics Modeling Learning Module to Improve Science Generic Skills on Momentum and Impulse Topics - Arifuddin, Muhammad; Fadillah, Muhammad Rashyid; Mahardika, Andi Ichsan (FKIP Universitas Lampung, 2025)
The Effect of Physics Modeling Learning Module to Improve Science Generic Skills on Momentum and Impulse Topics. The learning process dominated by lectures and the use of conventional teaching materials that are difficult for students to understand leads to low generic science skills in students. One-way, teacher-centered learning causes students to become passive. Meanwhile, abstract and quantitative material on momentum and impulse requires a conceptual and visual approach to make it easier for students to understand. Objectives: This study aims to determine the impact of using physics modeling learning modules on the improvement of generic science skills in impulse and momentum material. Methods: This study employed a quasi-experimental design with a one-group pre-test and post-test approach, applied to 34 students in class X.1, who served as research subjects at SMA Negeri 1 Alalak. The data were analyzed using n-gain scores and a paired sample t-test to determine the magnitude of the effect before and after treatment was administered. Findings: The analysis reveals that the use of effective physics modeling learning modules can enhance generic science skills, yielding an n-gain of 0.81. A substantial difference between the conditions before and after using the physics modeling learning module is also evident in the results of the paired sample t-test, which demonstrates how using the module affects students' development of generic science skills. Conclusion: Physics modeling learning modules have significantly and successfully enhanced students' generic science skills related to momentum and impulse content. Keywords: impulse, module, momentum, physics modeling learning, science, generic skills.